Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12529-015-9473-3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Impact of Physicians’ Occupational Well-Being on the Quality of Patient Care

Abstract: BackgroundIt is widely held that the occupational well-being of physicians may affect the quality of their patient care. Yet, there is still no comprehensive synthesis of the evidence on this connection.PurposeThis systematic review studied the effect of physicians’ occupational well-being on the quality of patient care.MethodsWe systematically searched PubMed, Embase, and PsychINFO from inception until August 2014. Two authors independently reviewed the studies. Empirical studies that explored the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 67 publications
(187 reference statements)
2
168
0
5
Order By: Relevance
“…23 Since 24 most error reduction programs have targeted inpatient settings. However, it is likely that the substantially broader scope of outpatient medicine would allow for far more errors and thus a greater impact if structural determinants of and activities for preventing outpatient mistakes could be discerned.…”
Section: Resultsmentioning
confidence: 99%
“…23 Since 24 most error reduction programs have targeted inpatient settings. However, it is likely that the substantially broader scope of outpatient medicine would allow for far more errors and thus a greater impact if structural determinants of and activities for preventing outpatient mistakes could be discerned.…”
Section: Resultsmentioning
confidence: 99%
“…Sixth, another potential confounder might be provider characteristics, for example, perceived responsiveness to patient requests or provider well-being. However, interpersonal behaviours and clinicians’ personality are of limited influence on patient perceptions of care,46 whereas occupational well-being of healthcare providers has a more profound effect on patient satisfaction 47…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review (Scheepers, Boerebach, Arah, Heineman, & Lombarts, 2015) identified 18 studies relating occupational well-being of physicians to quality of care. Occupational well-being was defined as a positive experience with or evaluation of one's work involving satisfaction, commitment, involvement, or engagement.…”
Section: Concluding Observationsmentioning
confidence: 99%